(untitled) (UNIZIK Journal of STM Education, 2026)
This study investigated the effect of the ethnomathematics teaching approach on senior secondary school students’ academic achievement in locus in Isoko North Local Government Area of Delta State, using Vygotsky’s (1978) Social Constructivist Theory. The study was guided by three research questions and three hypotheses tested at a 0.05 level of significance. The study adopted a quasi-experimental research design, specifically the pretest-posttest non-randomised control group design. The population of the study comprised 1,428 Senior Secondary School Two (SSII) students in public secondary schools in Isoko North Local Government Area. A sample of 252 students drawn from four intact classes in four selected public secondary schools was used for the study. The instrument for data collection was the Locus Achievement Test (LAT), which contained 50 multiple-choice items selected from past WAEC Mathematics question papers, from 2015 to 2025. The reliability of the instrument was established using the Kuder-Richardson Formula 21 (KR 21), and a reliability coefficient of 0.70 was obtained. Mean and standard deviation were used to answer the research questions, while Analysis of Covariance (ANCOVA) was used to test the hypotheses. The findings revealed that students taught locus, using the ethnomathematics teaching approach, achieved significantly better results than those taught using the lecture method. The findings also showed no significant difference between the achievement scores of male and female students taught using the ethnomathematics teaching approach, and no significant interaction effect between teaching approach and gender on students’ achievement in locus was observed. The study concluded that the ethnomathematics teaching approach is an effective and gender-inclusive teaching approach for improving students’ academic achievement in locus. It was therefore recommended among others that Mathematics teachers should adopt this approach in the teaching of locus and other Mathematics concepts in secondary schools.